Analisis Kuat Lentur Murni Sistem Balok Bataton Semi Pracetak - Bagus Rizkya putra; Ismeddiyanto Ismeddiyanto; Zulfikar Djauhari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Semi precast beam is unitary beam element that supports the load in longitudinal direction, the beam is unification of semi precast concrete with 5 MPa strength of precast concrete and cast in place with 17.5 MPa strength which were combined to create unified element of semi precast beam structure. Semi precast beams made the object of review using three beams type with dimensional variations as high as beam semi precast one layer was 140 mm, beam semi precast one layer 290 mm height, and beam semi precast two layers 290 mm height to be analyzed using finite element analysis Abaqus 6.12. Semi precast beams model will be given the burden of axial load has increased. Beams will be analyzed the influence of pure bending strength received by the relationship load - deflection parameters, the relationship moments - curvature and crack pattern that occurred three types of beams. Based on analysis results obtained with Abaqus 6.12 axial load greater value with increased dimensions and beams will be more stiffness. The maximum axial load value capable detained by the three types of semi precast beams at 8,61 kN for semi precast beams one layer was 140 mm height, 29.64 kN for semi precast beams one layer of 290 mm height and 25 kN for semi precast beam two layers of 290 mm height. Evaluation of cracking that occurs is cracked bending pure occur in areas of bending moment largest and in areas of tension on the beam.Keywords : Beam, semi precast, precast concrete, cast-in-place concrete, the finite element analysis